Evaluation of Fluoroquinolones for the Prevention of BK Viremia after Renal Transplantation - Gabardi, Steven (American Society of Nephrology, 2010)
Background and objectives: Nearly 30% of renal transplant recipients develops BK viremia, a prerequisite for BK nephropathy. Case reports have evaluated treatment options for BK virus, but no controlled studies have assessed prophylactic therapies. Fluoroquinolone antibiotics were studied for prevention of BK viremia after renal transplantation. Design, setting, participants, & measurements: This retrospective analysis evaluated adult renal transplant recipients with at least one BK viral load (blood) between 90 and 400 days after transplantation. Six to 12 months of co-trimoxazole was used for Pneumocystis prophylaxis. In sulfa-allergic/-intolerant patients, 6 to 12 months of atovaquone with 1 month of a fluoroquinolone was used. Fluoroquinolones can inhibit BK DNA topoisomerase. The two groups studied were those that received 30 days of levofloxacin or ciprofloxacin after transplantation and those that did not. The primary endpoint was BK viremia rates at 1 year. Of note, of the 160 patients not receiving fluoroquinolone prophylaxis, 40 received a fluoroquinolone for treatment of a bacterial infection within 3 months after transplantation. Subgroup analysis evaluating these 40 patients against the 120 who had no exposure to fluoroquinolones was completed. Results: A 1-month fluoroquinolone course after transplantation was associated with significantly lower rates of BK viremia at 1 year compared with those with no fluoroquinolone. In the subgroup analysis, exposure to fluoroquinolone for treatment of bacterial infections within 3 months after transplantation was associated with significantly lower 1-year rates of BK viremia. Conclusions: This analysis demonstrates that fluoroquinolones are effective at preventing BK viremia after renal transplantation.